Detection of an Optical/UV Jet/Counterjet and Multiple Spectral Components in M84 - Meyer, Eileen T.; Petropoulou, Maria; Georganopoulos, Markos; Chiaberge, Marco; Breiding, Peter; Sparks, William B. (IOP, 2018)
We report an optical/UV jet and counterjet in M84, previously unreported in archival Hubble Space Telescope imaging. With archival VLA, ALMA, and Chandra imaging, we examine the first well-sampled spectral energy distribution of the inner jet of M84, where we find that multiple co-spatial spectral components are required. In particular, the ALMA data reveal that the radio spectrum of all four knots in the jet turns over at approximately 100 GHz, which requires a second component for the bright optical/UV emission. Further, the optical/UV has a soft spectrum and is inconsistent with the relatively flat X-ray spectrum, which indicates a third component at higher energies. Using archival VLA imaging, we have measured the proper motion of the innermost knots at 0.9 ± 0.6 and 1.1 ± 0.4c, which when combined with the low jet-to-counterjet flux ratio yields an orientation angle for the system of {74}-18+9°. In the radio, we find high fractional polarization of the inner jet of up to 30% while in the optical no polarization is detected (<8%). We investigate different scenarios for explaining the particular multicomponent spectral energy distribution (SED) of the knots. Inverse Compton models are ruled out due to the extreme departure from equipartition and the unrealistically high total jet power required. The multicomponent SED can be naturally explained within a leptohadronic scenario, but at the cost of very high power in relativistic protons. A two-component synchrotron model remains a viable explanation, but more theoretical work is needed to explain the origin and properties of the electron populations.
Keywords: Astrophysics - High Energy Astrophysical Phenomena; galaxies: active; galaxies: jets